Zero-defect manufacturing terminology standardization: Definition, improvement, and harmonization - Sousa, João; Nazarenko, Artem; Grunewald, Christian; Psarommatis, Foivos; Fraile, Francisco; Meyer, Olga; Sarraipa, João (Frontiers in Manufacturing Technology, 2022)
Zero-Defect Manufacturing (ZDM) is the next evolutionary step in quality management for manufacturing that makes use of Industry 4.0 technologies to support quality in manufacturing. These technologies help to reduce the cost of inspection, allowing for more inspection points throughout the manufacturing process, reducing the size of quality feedback loops, and guaranteeing that no defective product is delivered to the customer. There are several ZDM-related initiatives, but still no harmonized terminology. This article describes the methodological approach to provide a common agreement on the ZDM concept and associated terminology taking place within an open CEN-CENELEC Workshop. The methodology has the support of ISO standards for terminology work such as ISO 704, ISO 860, and ISO 10241-1/2. This work shows that the terminology for ZDM has a significant overlap with the terminology of quality management, metrology, dependability, statistics, non-destructive inspection, and condition monitoring. The proposed new terms and definitions can be used to further extend ISO’s and IEC’s already available terminologies and support present and future researchers in the field to conduct their research using a common vocabulary.